Growth Performance of Khari Goats on Supplementation of Urea Molasses Mineral Block (UMMB) in Fodder Based Diets - Tiwari, MR egan; Shrestha, BK; Mandal, P; Panday, LN (Nepal Journal of Science and Technology, 2013)
Goat is important component of Nepalese farming system. Goat production and productivity in Nepal is not as their potential. One of the major factors causing low production and productivity of goats is lack of minerals in the diet. Therefore, to evaluate the mineral factor associated with low production and productivity of goats an experiment was carried out in growing male goats at Agriculture Research Station (Goat), Bandipur, Tanahun from February to March 2010. Ten male goats of 8-9 months of age and similar body weight were divided into two treatment groups having five animals in each group by using complete randomized design (CRD). Two types of diets were formulated for experimental animals. The animals of control group (treatment1) were provided seasonal fodder ad libitum plus concentrate mixture @ 1% of the body weight, whereas animals of treatment 2 were provided seasonal fodder and concentrate mixture same as in treatment1 plus UMMB @ 4% of the body weight. The study revealed that seasonal fodder and concentrate mixture intake of both groups was almost similar 2.0 kg and 207g, respectively and was not significantly difference in intake between diet groups. Similarly, total dry matter intake also was non-significant between diet groups. The highest body weight gain was observed in treatment 2 (3.86 ± 0.78 kg) than that of treatment1 (3.3 ± 0.90 kg). Body weight gain of the experimental animals was also found non- significant. Average daily gain (ADG) was recorded the highest in treatment 2 (85.77 g /day) in comparison to treatment1 (73.33 g/day). Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 29-32 DOI: http://dx.doi.org/10.3126/njst.v13i2.7710